The PGRS domain is responsible for translocation of PE_PGRS30 to cell poles while the PE and the C‐terminal domains localize it to the cell wall. Issue 6 (11th February 2014) - Chatrath, Shweta; Gupta, Vineet Kumar; Garg, Lalit C.
Abstract : PE_PGRS proteins localize in the mycobacterial cell wall and the cell wall localization of PE_PGRS33 has been shown to be attributed to its PE domain. In this study, we expressed deletion mutants of PE_PGRS30 in Mycobacterium smegmatis to characterize the role of its domains in protein localization. It was revealed that, apart from the PE domain, the C‐terminal domain present in few PE_PGRS proteins carries individual cell wall localization signals. Proteinase K sensitivity assay showed that PE_PGRS30 is exposed on the mycobacterial surface through its PGRS domain. PGRS domain was also shown to be responsible for polar localization of PE_PGRS30. Abstract : The role of PE_PGRS30 domains in protein localization. C‐terminal domain possesses individual cell wall localization signals. PGRS domain is exposed on cell surface. Polar localization is due to PGRS domain.